RACIAL DISCRIMINATION IN JERRY BRUCKHEMEIR'S GLORY ROAD MOVIE (2006); A MARXIST APPROACH - HARDIANTI, CHESARIA (2011)
The research is aimed to know the Haskin effort to attain racial discrimination in Jerry Bruckheime's Glory Road movie by using marxist approach. It is done by establishing two objectives: the first is analyzing the movie based on its structural elements and the second is analyzing the movie based on the marxist approach. The research is qualitative research. Type of data of the study is text and image taken from two data sources: primary and secondary. The primary data source is Glory Road movie directed by Jerry Bruckheimer released in 2006. While the secondary data sources are other materials taken from books, and internet related to the study. Both data are collected through library research and analyzed by descriptive analysis. The study comes to the following conclusions. First, based on the structural analysis of each elements, it shows that the character and characterization, casting, plot, setting, point of view, theme, mise en scene, cinematography, sound, and editing are related to each other and the unity . Second, based on the marxist analysis, the writer describes the result of research in which life is more meaningful if people uses it with unlimited creativity, there is also called freedom. Freedom here means the freedom of alienation, like working, especially in capitalis, human are spereted from their crativity, etc. He attains their team to change their social status from the lower to higher class.